Język agresji u dzieci z rodzin dysfunkcyjnych - Sileńska, Aleksandra; Szpunar, Kamila (Człowiek i Społeczeństwo, 2020)
Language of aggression, which is the subject of this article, is closely linked with the concept of aggression. Aggression is understood as any form of behaviour directed at causing damage or causing injury to another living creature. The article presents a pilot study about aggressive language and behaviour of children from dysfunctional families. Sample consisted of 12 children, aged 7 through 12, from dysfunctional families. Competent referees made observation of children’s language and behaviour using observation questionnaire. The observation took part during their activities at a community day care social centre. The result showed that referees agreed that the children from the study sample often used aggressive language and behave aggressively. There is a lack of this kind of studies.